Análise do Programa Institucional de Bolsa de Iniciação à Docência (PIBID)/CAPES (2007/2019) na perspectiva do ciclo de políticas - SILVA, Carla Christina Soares Guedes da (2021)
This research aims to present results from the Institutional Program for Teaching Initiation Scholarships (PIBID) as a program for initial teacher education in Brazil from its inauguration in 2007 until 2019. For this purpose, the official documents of the Ministry of Education, more specifically, the Coordination for the Improvement of Higher Education Personnel / CAPES, responsible for its operation. Thus, it is intended to contribute to studies on public policies in education in Brazil, in particular teacher training policies. It started from the understanding that PIBID, among other things, aims to interfere in initial training in undergraduate courses and, through its insertion in public schools, also to favor their “quality”. As a general objective of this study we intend to analyze the trajectory of the Institutional Program for Teaching Initiation Scholarship - PIBID, considering the speeches, results and effects, from the official texts (public notices and management reports from CAPES, between 2007 and 2019), bringing from the perspective of the Policy Cycle of Stephen Ball and Richard Bowe (MAINARDES, 2006). To answer this broader objective, we have as specific objectives: Conceptualize the Educational Policies and the Policy Cycle of Stephen Ball and Richard Bowe; To present, in general lines, the debate on teacher education; Present the context of influence, which deals with the historical moment that precedes the creation of the Program; Analyze speeches in the program text and results and effects in official documents. As a result of the analysis of the reports, it was possible to observe that in 2007, the year the program began, 3,088 scholarships were offered; in 2014 this number rose to 90,247 PIBID scholarships in Brazil; and in 2019, the year of the last report analyzed, the number of scholarships had reduced to 48,277. PIBID is related to teacher training as a public policy. It presents formative strategies, it becomes interesting to be analyzed, as we realize that these were drawn from clashes over teacher training. Therefore, we decided to analyze the documents to assess the extent of the Program's effects and results over the years.